Comparison Of Severity Of Non-Hemorrhagic Stroke With Diabetes Mellitus (DM) Type 2 And Without Diabetes Mellitus (DM) Type 2 Based On NIHSS - Sulistiani. M, Nurul Ariva; Handayani, Fitriah; Liwang, Muh. Nur Ikhsan; Salman, Mohammad (Jurnal EduHealth, 2022)
A stroke is a disease or functional problem of the brain that manifests as nerve paralysis due to a blockage in the blood supply to the brain. Acute stroke is a brain disorder caused by the interruption of blood flow to the brain due to a blockage (ischemic stroke) or hemorrhage (hemorrhagic stroke). Individuals with diabetes mellitus with ischemic stroke exhibit a distinct clinical pattern and a more favorable neurovascular outcome than patients without diabetes. Objective: to compare the severity of non-hemorrhagic stroke between individuals with Diabetes Mellitus (DM) Type 2 and those without Diabetes Mellitus (DM) Type 2 using The National Institutes of Health Stroke Scale (NIHSS). Methods: Analytical observational research design with a retrospective methodology. 30 responders were divided into 15 stroke patients with Diabetes Mellitus (DM) Type 2 and 15 stroke patients without Diabetes Mellitus (DM) Type 2. The average value or mean rank for the Stroke group with Diabetes Mellitus (DM) Type 2 was 18.77, while it was 12.23 for the Stroke group without Diabetes Mellitus (DM) Type 2. The P-Value for the test is 0.076. Results The P value is greater than 0.05, indicating that there is no significant difference between stroke with Diabetes Mellitus (DM) Type 2 and stroke without Diabetes Mellitus (DM) Type 2 with regard to severity. As stated previously, the outcomes can be affected by the risk factor of Diabetes Mellitus (DM) Type 2, which comprises of multiple risk factors that can have an effect.